دراسة مقارنة بين بيت الزكاة الكويتي وصندوق الزكاة الإماراتي في إدارة أموال الزكاة : دراسة تحليلية في ضوء القرآن والسنة - منصوري، سعيد علي سعيد الوحيري (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2022)
This study is a comparison between two Zakat institutions in the Arab Gulf states, namely the Zakat Fund Foundation in the United Arab Emirates and the Zakat House Foundation Kuwait. It examines how these institutions collect and distribute Zakat and the difficulties they face in achieving their goals. The aim of this comparison is to know the strengths and weaknesses of each of these two institutions and to provide recommendations for the development of the Zakat Fund Foundation. Among the difficulties that the two institutions share in common is the lack of zakat funds and donations due to inadequate government support and incompetence at work. The researcher used three approaches namely, the comparative approach to compare between the Zakat Fund Foundation in the Emirates and the Zakat House Foundation Kuwait regarding the collection and distribution of Zakat and the difficulties they encounter in achieving their goals.; the inductive approach to extract the texts from the books ; and the descriptive analytical approach to analyze the answers to the questionnaire questions about Zakat. This study has found that - there is a decrease in the annual fund imports of Zakat (an average of 155 million dirhams) as compared to the Zakat funds due in the UAE (6 billion dirhams), where the total amount of Zakat Fund does not exceed 2.6%. This is due to several reasons including: the Zakat collection is voluntary and there are many charitable institutions in the United Arab Emirates that receive Zakat funds. The study has shown that the compulsory payment of Zakat in Kuwaiti law contributed to the increase in Zakat House's imports of Zakat funds. Also, the Zakat Fund Foundation in the Emirates limits its activities to the collection and distribution of Zakat funds inside the country; it does not involve in other charitable projects, such as the construction of mosques, digging of wells and orphan sponsorship.